Amphibacillus Marinus Sp. Nov., a Member of the Genus Amphibacillus Isolated from Marine Mud - Pugin, B (2013)
A Gram-positive, spore-forming, rod-shaped bacterium, designated J1T was isolated from deepsea mud collected from the South China Sea and subjected to polyphasic taxonomic investigation. Phylogenetic analysis based on 16S rRNA gene sequences revealed that J1T clustered with the type strains of Amphibacillus cookii, Amphibacillus sediminis and Amphibacillus jilinensis and exhibited a range of similarity of 93.9-97.0% to members of the genus Amphibacillus. The DNA G+C content was 36.7 mol%. Chemotaxonomic analysis showed no quinones, and the cell wall contained meso-diaminopimelic acid as the diagnostic diamino acid for strain J1T. The major cellular fatty acids were iso-C15:0 and anteiso-C15:0. Strain J1T was positive for catalase activity and negative for oxidase activity. On the basis of phylogenetic position and phenotypic properties, strain J1T represents a novel species of the genus Amphibacillus and the name Amphibacillus marinus sp. nov. is proposed. The type strain is J1T (=CGMCC 1.10434T=JCM 17099T). © 2013 IUMS Printed in Great Britain.